The Hundred Years’ War on Palestine, Rashid Khalidi - Arhama Siddiqa (CISS Insight Journal, 2024)
“The Hundred Years’ War on Palestine” by Rashid Khalidi, a renowned Palestinian historian, marks his eighth work on the Middle East and represents his most introspective endeavor. Individuals from various fields of study and the general public will find this information beneficial. Readers with a penchant for delving into historical narratives will find this book captivating, as it offers a unique perspective on the lived experiences of those involved in the resistance movement. This book holds great significance today as it draws striking comparisons to events that have unfolded since 7 October 2023. Khalidi extensively employs 459 footnotes to document all the issues he references meticulously. His book strongly focuses on personal experiences, intertwining intimate family anecdotes, contemplating his diverse extended family, and encompassing various regions. The Khalidi family has been deeply involved in observing and analyzing Palestine’s complex history. The personal stories support the findings derived from his academic research and firsthand experience of historical events.